DIFFERENCES IN THE EFFECTS OF CIRCUIT TRAINING AND INTERVAL TRAINING ON IMPROVEMENTS IN 50-METER BREASTSTROKE SPEED AMONG ATHLETES AT THE XANDRIA SWIMMING CLUB - Evlyne Keriahenta Br Brahmana; Saipul Ambri Damanik; Muhammad Yan Ahady (Universitas Negeri Medan, 2026)
This study aimed to determine the difference in effect between circuit training and interval training on increasing 50-meter breaststroke swimming speed in Xandria Swimming Club athletes. This research used a quasi-experimental method with a two-groups pretest-posttest design. The sample consisted of 20 athletes selected through purposive sampling and divided into two groups using ordinal pairing technique. Group A received circuit training while Group B received interval training for 16 sessions. The instrument used was a 50-meter breaststroke swimming test. Data analysis employed t-test at a significance level of . The results showed: circuit training had a significant effect with p < 0.001 and an average time reduction of 5.704 seconds; interval training also had a significant effect with p < 0.001 and an average time reduction of 5.761 seconds; however, there was no significant difference between the two methods (Sig. 2-tailed 0.955 > 0.05). In conclusion, both training methods have an equivalent level of effectiveness in improving 50-meter breaststroke swimming speed.